The Role of Merapi FM Community Radio in Disaster Mitigation At Merapi Slope Residential Area Cluntang, Musuk, Boyolali - Topan Setiawan; Sri Hartini; Fanny Hendro Aryo Putro; Wahyuning Chumaeson (PT Publikasiku Academic Solution, 2024)
The purpose of this study was to determine the role of Merapi FM community radio in reducing disaster risk in the potential disaster exposure area of the Musuk Boyolali sub-district. This research method is empirical research or field research with a qualitative approach. Qualitative research is research that produces descriptive data in the form of written or spoken words from people and behaviour that can be understood. This approach is data collection in the form of oral, written, and also in the form of image documentation. Data from a qualitative descriptive approach can come from interviews, photographs, field notes, video recordings, memos and official documents. The results showed that the community plays an active role in disaster risk reduction efforts in the Cluntang area, namely through disaster response training, environmental preservation, trauma healing, and regional arts and culture. Based on the results of the research, the role of Merapi FM community radio in mitigation and disaster risk reduction in the Cluntang area is (1) Carrying out its role and function by facilitating the needs of the community to reduce the risk of the Merapi disaster, (2) Mobilising the community to be directly involved in all activities, starting from on-air and off-air activities.